Energy performance of PVC-Coated polyester fabric as novel material for the building envelope: Model validation and a refurbishment case study. (September 2021) - Ciampi, Giovanni; Spanodimitriou, Yorgos; Scorpio, Michelangelo; Rosato, Antonio; Sibilio, Sergio
Abstract: Tensile materials are concurrently becoming more and more utilized in contemporary architecture design, despite a lack of experimental testing and numerical model development to assess their actual effect on the building behavior, even more, if considered integrated in a second-skin system. In this research, the PVC-coated polyester fabric has been selected and tested as tensile second-skin material by using two outdoor comparative test cells to evaluate its performance and to calibrate and validate a numerical model in TRNSYS 18. Then, the validated numerical model has been used in a case study as a second layer in a flexible façade system. In particular, a simulation refurbishment of a typical three-story office building, located in southern Italy, has been investigated with the aim to evaluate its potential benefits from an energy point of view. The results showed that the refurbishment by means of a second-skin system always allows for an energy saving, up to a maximum of 6.1%; also, by exploiting the semi-transparency and the flexibility offered by this material to implement a continuous whole-façade design on the south wall, thus covering with the second-skin both the walls and the openings, the solar gains across the year can be modulated, by minimizing the gains during the summer and maximizing them during the winter, consequently leading to a reduction of the cooling and heating energy demands, for an overall heating energy demand reduction of about 9.8%. Highlights: A tensile second-skin material is tested by using outdoor comparative test cells. A simulative model of the tensile second-skin material is developed and validated. The developed model is used in a refurbishment of a typical Italian office building. The indoor air temperatures decrease 1.23 °C using the proposed second-skin system. The proposed refurbishment allows a primary energy reduction of about 6.0%.